1990
DOI: 10.1002/etc.5620091105
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic environmental fate of nitroguanidine

Abstract: The environmental fate of nitroguanidine (NQ) in surface waters is dominated by photolysis with surface half‐lives at 40°N ranging from 0.6 d in summer to 2.3 d in winter. The environmental quantum yield is 0.01. The NQ is initially photolyzed to nitrite and hydroxyguanidine; nitrite is photochemically converted to nitrate and hydroxyguanidine undergoes sensitized photolysis to unknown products. The photooxidation of nitrite is assisted by organic material in a process not involving H2O2 or singlet oxygen. Nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
1

Year Published

1991
1991
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 15 publications
(12 reference statements)
3
38
1
Order By: Relevance
“…For NQ, photodegradation products previously identified include nitrosoguanidine, hydroxyguanidine, and cyanoguanidine, which, after further irradiation, terminate in nitrite, nitrate, ammonia, urea, guanidine, cyanamide, nitrosamide, and melamine [18,19,37]. Cyanoguanidine potentially converts to cyanide under acidic conditions, such as those found after prolonged photodegradation experiments at elevated concentrations [38].…”
Section: Discussionmentioning
confidence: 99%
“…For NQ, photodegradation products previously identified include nitrosoguanidine, hydroxyguanidine, and cyanoguanidine, which, after further irradiation, terminate in nitrite, nitrate, ammonia, urea, guanidine, cyanamide, nitrosamide, and melamine [18,19,37]. Cyanoguanidine potentially converts to cyanide under acidic conditions, such as those found after prolonged photodegradation experiments at elevated concentrations [38].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the large absorptivity in the UV region, NQ is amenable to photo degradation, especially by UV light. 23,56,80 We found that after four hours of photolysis, NQ absorbance decreased, but an increase in absorbance was observed below 225 nm ( Figure 34B).…”
Section: Probing Mechanisms Of Direct Photolysismentioning
confidence: 92%
“…There are conflicting reports about the organic products from NQ photolysis, including cyanamide, hydroxy-guanidine, or more recently, stoichiometric guanidine. 23,56,80 NTO apparently produces CO2 or other volatile organics upon extended irradiation, with another study finding hyrdoxy-triazolone and potential nitric oxide formation. 23,74 Given the conflicting reports of photolysis products and mechanisms, along with the surprising renitration of guanidine to form NQ, our purpose was to investigate the conditions under which NQ and NTO are photolyzed.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations